METASOMATIC GARNET-CLINOPYROXENE-ORTHOPYROXENE-HORNBLENDE VEINS IN METAANORTHOSITES OF THE KOLVITSA MASSIF, KOLA PENINSULA: MINERAL COMPOSITION AND RELATION WITH SYNGRANULITE GRANITIZATION - Khodorevskaya L.I.; Korikovsky S.P. (My University, 2007)
Forms and scales of transportation and redeposition of significant amounts of Mg, Fe, and Ca, which are removed during granitization and debasification of metamorphic (mainly mafic) rocks, is one of the least studied problems in the petrology of granite gneiss and migmatite complexes. Study of these complexes revealed the absence of an uninterrupted basification front before granitization zones inferred from idealized models. This is consistent with the conclusion of Korzhinsky and subsequent studies suggesting that Mg, Fe, and Ca removed during granitization are commonly scattered far beyond the aureoles of anatectic granitization.